STUDY ON CONNSTRUCTION OF PUKAT TERI IN KM. INKAMINA AT TANJUNG TIRAM VILLAGE BATUBARA DISTRICT OF NORTH SUMATRA - Syofyan, Irwandy; ', Hermawanto; ', Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted on 17-25 April 2016 in KM. INKAMINA. The purpose of this study to collate the information of pukat teri construction. The method used was a survey method. Results from this research showed that the pukat teri construction has 355m length and 40m depth. The net using materials PA (Polyamide) multifilament. Buoy, ris, sinker and wrinkles rope using the same materials was PE (polyethylene). 1350 floats materials styrofoam, 1550 sinker materials lead, 173 rings materials iron. In terms of construction, pukat teri gear same with purse seine, reinforced by a wrinkles and rings rope in to The characteristics of the purse seine.Keywords :Pukat teri, construction, Tanjung Tiram